Hunter selection and long‐term trend (1881–2008) of red deer trophy sizes in Hungary. Issue 1 (4th December 2012) - Rivrud, Inger Maren; Sonkoly, Krisztina; Lehoczki, Róbert; Csányi, Sándor; Storvik, Geir Olve; Mysterud, Atle; Toit, Johan du
Summary Human harvesting has a large impact on natural populations and may cause undesirable life‐history changes. In wild ungulate populations, unrestricted trophy hunting may cause strong selection pressures resulting in evolutionary change towards smaller trophies. It has rarely been tested how harvesting selection varies in space and time, and whether directional hunter selection is sufficiently strong to induce long‐term decreases in trophy size in century‐scale data. We analysed two unique data sets of harvesting records spanning decade (1973–2008) and century scales (1881–2008) to identify changes in trophy size and how harvesting selection varies in space and time in red deer Cervus elaphus. We contrasted predictions from the trophy‐hunting depletion, the restricted trophy hunting and the hunting pressure hypotheses. Foreign hunters selected older and larger males than local hunters, but selection patterns for age‐specific trophy size between counties and over time were dynamic. Patterns of red deer trophy size development from exhibitions (representing the 'upper tail' of antler sizes) were remarkably similar across Hungary from 1881 to 2008. A weak decline in trophy size between 1881 and 1958 was followed by a strong increase in trophy size between 1958 and 1974, culminating in a period of stable antler tine numbers and a weak decline in beam length until 2008. We rejected the trophy hunting depletion hypothesis due to the increase in trophy size after a period of decline; patterns were most consistent with the hunting pressure hypothesis. Large increases in trophy size during 1958–1974 were likely due to a relief in hunting pressure due to implementation of strict management regulations allowing stags to grow old after the massive overharvesting during World War II, but we cannot exclude impacts from environmental factors, and that data from trophy exhibitions may underestimate trends. Synthesis and applications. Trophy hunting does not necessarily lead to a non‐reversible decline in trophy size, even over century‐long time‐scales. To ensure sustainable trophy hunting management, we need to consider factors such as spatial and temporal refuges, compensatory culling, saving stags until prime‐age culmination and higher prices for larger trophies.